1983
DOI: 10.1111/j.1476-5381.1983.tb10045.x
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct interactions of barbiturates and chlormethiazole with the GABAA receptor complex in rat cuneate nucleus in vitro

Abstract: 1Some pharmacological properties of the GABAA receptor complex in the rat cuneate nucleus slice have been assessed from depolarization responses to the y-aminobutyric acid (GABA) analogue muscimol and antagonism of the responses by bicuculline and picrotoxin. 2 Responses to muscimol were potentiated by the following drugs, in descending order of potency with regard to the concentrations required in the Krebs medium:Primidone and phenylethylmalonamide were inactive. Calculation of the concentrations likely to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Several compounds which enhance inhibitory processes in the hippocampus have been shown to have some neuroprotective effect, particularly when treatment is initiated around the time of the ischaemic episode (Kirino et al, 1986;De Leo et al, 1988;Alps et al, 1988;Taft et al, 1989). Chlormethiazole is an anticonvulsant, sedative and hypnotic drug (Ogren, 1986;Green & Murray, 1989), which acts at the y-aminobutyric acid (GABA) receptor both to potentiate the effects of GABA and to modulate channel opening directly (Harrison & Simmonds, 1983;Moody & Author for correspondence. Skolnick, 1989;Cross et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds which enhance inhibitory processes in the hippocampus have been shown to have some neuroprotective effect, particularly when treatment is initiated around the time of the ischaemic episode (Kirino et al, 1986;De Leo et al, 1988;Alps et al, 1988;Taft et al, 1989). Chlormethiazole is an anticonvulsant, sedative and hypnotic drug (Ogren, 1986;Green & Murray, 1989), which acts at the y-aminobutyric acid (GABA) receptor both to potentiate the effects of GABA and to modulate channel opening directly (Harrison & Simmonds, 1983;Moody & Author for correspondence. Skolnick, 1989;Cross et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Harrison & Simmonds (1983) have already observed this effect with alfaxalone in the cuneate slice. Also they have drawn attention to the dissociation of potentiation of responses to GABA by anaesthetic barbiturates, in the presence and absence of picrotoxinin, and the ability of agents such as chlormethiazole and anticonvulsant barbiturates to reverse the picrotoxinin-induced depression of maximal responses to GABA whilst showing minimal potentiating action (Harrison & Simmonds, 1983). In this regard, alfaxalone resembles anaesthetic barbiturates rather than the latter anticonvulsants.…”
Section: Discussionmentioning
confidence: 80%
“…Not all studies show major differences between the agents. For example, both barbiturates and alphaxalone enhanced depolarizing responses to GABA and muscimol in the rat cuneate nucleus slice with little effect on responses to glycine (Harrison & Simmonds, 1983;, which has been interpreted in terms of the interactions with the GABAA-receptor complex . The question that has to be asked about any study on an individual part of the nervous system is whether the particular effects observed are critical for the production of anaesthesia in the whole animal.…”
Section: Resultsmentioning
confidence: 99%